Homework Help

Solve for m: `S = H/m(a-b)`

kristenmariebieber's profile pic

Posted via web

dislike 2 like

Solve for m:

`S = H/m(a-b)`

1 Answer | Add Yours

mjripalda's profile pic

Posted (Answer #1)

dislike 1 like

`S=H/m(a-b)`

To get m only at one side of the equation, multiply both sides by m.

`S*m=H/m(a-b)*m`

 

`S*m=H(a-b)`

And then, divide both sides by S.

`(S*m)/S=(H(a-b))/S`

 

`m=(H(a-b))/S`


Hence,  `m=(H(a-b))/S` .

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes